Vitamin D and its relationship to performance and health during a competitive period in elite women's basketball and volleyball players - Miguel Ortega, Álvaro; Calleja González, Julio; Mielgo Ayuso, Juan (Wiley, 2025)
Vitamin D [25(OH)D] is a key nutrient, although its level is often low in the general population. To investigate the relationship between vitamin D levels and muscle performance, and to analyze how vitamin D changes during a 16- week competitive season and its relationship to the performance tests performed. Participant characteristics: age 25.1±4.7 years; height 1.8±0.1m, and body mass 73.9±15.4kg. Vitamin D levels (ng/mL) were at T1 (September): 33.7±14.7 (n=23), and at T2 (January): 26.1±7.3 (n=23). Over 16weeks of competition, participants' blood was analyzed to determine their vitamin D levels. Their athletic abilities were evaluated through various tests: vertical jumps (standing jump and countermovement jump); 20-m sprint without direction changes; and intermittent endurance test; the vitamin D level decreased from T1 to T2 by ¿22. 40% [p<0.05] but performance improved in all tests performed (SJ: 4.57%; CMJ: 6.94%; VO2max: 4.99% [p<0.05]; 20m: ¿1.83%). There is a relationship between vitamin D levels and physical performance in female indoor athletes. The results suggest that increased training load may also negatively affect vitamin D levels in elite female indoor athletes. KEYWORDS female, indoor, performance, vitamin D
Keywords: female, indoor, performance, vitamin D